HUMAN FACTS IN THE FILM “WADJDA” BY HAIFAA AL-MANSOUR: A GENETIC STRUCTURALISM ANALYSIS - Nisrina Zahrani Salsabila; Rohanda Rohanda; Gia Ramadhan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Film is a form of visual art that serves not only as a medium of entertainment but also as a reflection and critique of the social realities that underpin it. This study aims to analyse how the film Wadjda (2012) by Haifaa al-Mansour represents individual struggle and oppressive social structures through the lens of genetic structuralism developed by Lucien Goldmann. The primary objective of this research is to reveal the dialectical relationship between the film text and the patriarchal social structure of Saudi Arabian society by examining how collective consciousness is reflected in the narrative and characters of the film. The focus of the study lies in two main aspects: (1) the individual facts depicted in Wadjda and (2) the social facts that underlie the limitations of women's roles in society. Through narrative and social analysis of the film Wadjda, it is found that Wadjda's struggle to own a bicycle becomes a symbol of resistance against cultural and religious norms that restrict women's freedom. The film not only portrays the personal conflict of the character but also represents the tension between traditional values and aspirations for modernity. The findings of this study are expected to contribute to literary studies, particularly in understanding the dialectical relationship between text and social structure in visual literary works.